Pembinaan Pelaksanaan Fardu Kifayah dan Pelatihan Imam Anggota Muhammadiyah (Studi Pimpinan Cabang Muhammadiyah Medan Deli) - Zailani Zailani; Nurman Ginting (University of Muhammadiyah Sumatera Utara, 2019)
This service is coaching for Muhammadiyah members in PCM of Medan Deli. It is hoped that from fardhu kifayah training and Imam training there will be a collective awareness of the importance of knowledge and skills in carrying out special worship. This service was partnered with the PCM of Medan Deli and Leadership of Majelis Tablig of Muhammadiyah Medan Deli. These two partners have different responsibilities. For the PCM of Muhammadiyah Medan Deli, he was responsible for the policy of ordering the three Branches under his guidance, namely the Ranting of Tanjung Mulia, Hilir, Tanjung Mulia Darat and Mabar to be able to send training participants to implement fardhu kifayah and imam. Whereas the Medan Deli Tabligation Assembly has authority in operational aspects. The method used includes lectures, discussions, questions and answers and simulations. The target is to be achieved, the participants understand well about the ins and outs of the implementation of fardhu kifayah. As for the imam, the emergence of awareness that not all pilgrims have the ability to become imam.